Rancang Bangun Aplikasi Sistem Elektronik Recruitment Karyawan Berbasis Web di PT. Lestari Abadi Sakti - Alfaridzi, Achmad; Dwi Yulianti Kusuma, Susanna (CV. Multi Kreasi Media, 2024)
In the process of accepting new employees, sometimes the problem that arises in the recruiter process is the large number of incoming spam email messages which becomes an obstacle for recruiters to find candidates according to the criteria requested by the company. However, it would be easy if there was a system that could help recruiters to help find new employees with the competencies possessed by prospective employees. With the design of this website-based e-recruitment application, it will make it easier for recruiters to validate files owned by prospective employees and the system development development method used in making this application is the prototype method which is a software development method that allows interaction between developers. System with system users, so as to overcome incompatibility between developers and users. The results of this research will be used by the HRD team of PT Lestari Abadi Sakti to carry out recruitment process activities with a Web-based application that has been created. So that the recruitment process activities will run more effectivel.